Envy in response to help: A helping as status relations model - TAI, Kenneth (Institutional Knowledge at Singapore Management University, 2019)
Social exchange theory suggests that after receiving help, peopleexperience gratitude and they reciprocate by helping the original help giver.However, it remains unclear whether people experience other emotions that drive positive reciprocation after receiving help.Building on helping as status relations framework, we suggest that when higherperformers provide task-related help to lower performers, help recipients perceivethat help givers have higher status, and respond to the help with envy. Torebalance the status relation, help recipients are motivated to reciprocate byhelping the help giver. Results from three studies progressively support our predictionsthat help recipients respond with envy when they receive task-related help, butonly toward higher performing help givers. Furthermore, envious help recipientswho have higher internal locus of control are more likely to give reciprocalhelp. The findings support the helping as status relations model by demonstratingthat envy plays a unique role, over and beyond gratitude.